2000
DOI: 10.2754/avb200069040311
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Craniocaudal Instability in Stifle Joints of Dogs Using Stress Radiographs

Abstract: Craniocaudal stifle joint laxity in dogs affected by various stifle disorders was determined using mediolateral X-ray projections of the stifle joint in neutral and tibial compression stress position. In all, 129 stifle joints of 80 dogs were included in the study.Patients were classified into following groups characterised by: 1) total cranial cruciate ligament (CCL) rupture, 2) total CCL rupture and medial meniscus lesion, 3) partial CCL rupture, 4) partial CCL rupture and medial meniscus lesion, 5) clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…We also did not prove a rise in the risk of medial meniscal damage in relation to the growing joint laxity (measured by radiography in our study). It is in accordance with other papers (D e Rooster et al 1998;Zatloukal et al 2000) which did not prove a difference in the instability of the joint with medial meniscal damage and intact ones. On the basis of our study (and some others) it seems that the grade of joint instability is not a decisive factor for the meniscal damage.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We also did not prove a rise in the risk of medial meniscal damage in relation to the growing joint laxity (measured by radiography in our study). It is in accordance with other papers (D e Rooster et al 1998;Zatloukal et al 2000) which did not prove a difference in the instability of the joint with medial meniscal damage and intact ones. On the basis of our study (and some others) it seems that the grade of joint instability is not a decisive factor for the meniscal damage.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding the fact that all radiographs were evaluated by one radiologist (Zatloukal), we can consider even these subjective criteria to be uniform and sufficient for our study. Comparing the neutral mediolateral and stress tibial compression projections we determined the index of laxity of the stifle joint using the technique by Zatloukal et al (2000). Stifle joints were classified into three groups (<25, 25-50, >50) using the index of laxity.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies evaluating for a distance change in serial radiographs for CTT also have not found a correlation with meniscal status. These studies have had low numbers of cases with meniscal tears (less than 20 total) [5,25]. Our population contained 162 cases with meniscal tears providing stronger support for a lack of correlation and reducing the potential for a type II error.…”
Section: Plos Onementioning
confidence: 91%
“…have a relatively higher degree of instability versus partial CCL rupture [5,8,25]. Our study population included a higher number of dogs with complete CCL rupture than partial CCL rupture with only two of the dogs with partial CCL rupture exhibiting spontaneous radiographic CTT.…”
Section: Plos Onementioning
confidence: 99%
“…This combination induces deep sedation, sufficient for performing procedures of intermediate level of pain, such as radiography of the hip and stifle joint instability (Neãas and Toombs 1999;Toombs and Neãas 1999;Zatloukal et al 2000). Sufficient analgesia and muscle relaxation is essential for such examinations because it enables measurement of the passive joint laxity.…”
Section: Discussionmentioning
confidence: 99%